1997
DOI: 10.2172/658117
|View full text |Cite
|
Sign up to set email alerts
|

A study of the behavior of bromide in artificial pits using in situ X-ray microprobe analysis

Abstract: An in situ x-ray microprobe analysis of Type 316 stainless steel amficial pits has been canid out with bromiddchloride solution. A high intensity 8 pm diameter polychromatic x-ray beam was scanned across the steellsolution interface within the artificial pit. The resulting x-ray fluorescence was analyzed using an energy dispersive x-ray detector. In contrast to the light Cl atom, Br could be detected, making it possible to monitor the behavior of halides in the amficial pits and in the salt layer at the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…This is consistent with the other study which showed higher concentrations near the interface and it was reportedly caused by lower diffusion coefficient of ions near the interface. 7,8) In this study, the deviation was not so clear as reported, which can be attributed to a relatively larger beam size of 0.1 mm in height. …”
contrasting
confidence: 66%
See 4 more Smart Citations
“…This is consistent with the other study which showed higher concentrations near the interface and it was reportedly caused by lower diffusion coefficient of ions near the interface. 7,8) In this study, the deviation was not so clear as reported, which can be attributed to a relatively larger beam size of 0.1 mm in height. …”
contrasting
confidence: 66%
“…It was reported that 1.08 M of chromium ion was close to the dissolving interface of an artificial pit for Type304 SS in 0.5 M HCl and 0.5 M NaCl solution, higher than that observed in this study. 7,8) In the reported experiments, stainless steels were dissolving with salt films on the surface, therefore the difference of concentration of chromium ions near the dissolving interface might arise from the difference of solubility of metal chlorides and bromides. Solubility of metal chlorides were estimated as 5.02 M, 7,8) but solubility for metal bromide has not been obtained yet.…”
Section: Concentration Of Chromium and Bromide Ions In-mentioning
confidence: 99%
See 3 more Smart Citations